2016
DOI: 10.1007/s12011-016-0720-5
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Serum Copper Levels in Patients with Major Depressive Disorder

Abstract: Copper may be involved in the pathophysiology of depression. Clinical data on this issue are very limited and not conclusive. The purpose of the study was to determine the copper concentration in the serum of patients with major depressive disorder and to discuss its potential clinical usefulness as a biomarker of the disease. A case–control clinical study included 69 patients with current depressive episode, 45 patients in remission and 50 healthy volunteers. Cu concentration was measured by electrothermal at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 30 publications
3
20
0
2
Order By: Relevance
“…No differences in Cu concentrations were demonstrated between the BD and MD [44]. The Cu levels were found similar in depressive patients (both with a current depressive episode and in remission) and HC group [45]. Elevated levels of blood Cu were reported in depressive disorder with a probable role of Cu as a biomarker of depression by a recent review [46].…”
Section: Discussionmentioning
confidence: 89%
“…No differences in Cu concentrations were demonstrated between the BD and MD [44]. The Cu levels were found similar in depressive patients (both with a current depressive episode and in remission) and HC group [45]. Elevated levels of blood Cu were reported in depressive disorder with a probable role of Cu as a biomarker of depression by a recent review [46].…”
Section: Discussionmentioning
confidence: 89%
“…Studies have observed a potential association between levels of free copper in blood and cognitive impairment [28]. Although inconclusive results have been reported [29], one study also suggests a relationship between elevated copper levels and depression [30]. The identi ed adverse reactions illustrate the importance of follow-up consultations with the aim to identify those who develop adverse reactions.…”
Section: Discussionmentioning
confidence: 99%
“…They also performed another study (Varconyl et al, 2011) and reported a high prevalence of copper deficiency and its association with iron status, which is consistent with our results. The mean copper level is normally between 100-130 mg/100 ml of the serum (Styczeń et al, 2016).…”
Section: Discussionmentioning
confidence: 99%